The Flight Instructor's Survival Guide : true, witty, insightful stories illustrating the fundamentals of instructing. - McMahon, Arlynn (Aviation Supplies & Academics, Inc., 2017)
Memorable stories and sage advice illustrating the fundamentals of instruction in aviation training.